Efeito de uma fosfolipase A2 Lisina 49, ACL miotoxina, do veneno da serpente Agkistrodon contortrix laticinctus sobre o transpote de água em bexiga urinária isolada de sapo - Leite, Renner de Souza (2004)
ACL myotoxin (ACLMT) is a Lys49 phospholipase A2-like protein isolated from the venom of the snake Agkistrodon contortrix laticinctus. The aim of this work was to study the effect of ACLMT on water transport in the toad urinary bladder. Water flow through the membrane was measured gravimetrically in bag preparations of the bladder. ACLMT increased the baseline water flow and partially inhibited the water permeability stimulated by arginine-vasopressin (AVP), cyclic AMP, 8-chlorophenylthio-cAMP and forskolin. The effect of ACLMT on baseline water flow was prevented by lanthanum, nifedipine, and trifluoperazine. These results suggest that the effect of ACLMT on baseline water flow could be mediated either by an increase in intracellular calcium or by the activation of the calcium-calmodulin. Colchicine reduced the effect of ACLMT on baseline water permeability. Carbachol has been shown to enhance baseline water flow while inhibiting AVP-stimulated water flow by increase in intracellular calcium. The effects of ACLMT and carbachol on baseline and AVP-stimulated water flow were not additive, suggesting that both agents alter the water transport by a similar mechanism. Lanthanum reduced the inhibitory effect of ACLMT on AVP-stimulated water permeability, suggesting the participation of intracellular calcium in this effect. Indomethacin reduced the effect of ACLMT on forskolinstimulated water flow, suggesting a role for prostaglandin in the effect of ACLMT on AVP-stimulated water permeability. However, the inhibitory effect of ACLMT on AVP-stimulated water flow was enhanced in the presence of trifluoperazine. Similarly, the inhibitory effect of ACLMT on AVP and cAMP-stimulated water flow was enhanced in the presence of colchicine. Therefore, the results of present study suggest that the effects of ACLMT on water permeability could be mediated either by an increase in intracellular calcium or by the activation of the calciumcalmodulin, and also suggests a role additional for prostaglandin in effect of ACLMT on AVP-stimulated water transport. In addition, the effect of ACLMT on water transport seems be dependent of integrity of microtubules.